การวางแผนเพื่อป้องกันและบรรเทาการเกิดอัคคีภัย : กรณีศึกษา เขตคลองเตย กรุงเทพมหานคร - วรรณลิกา พรหมจรรยา (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
The purpose of the thesis is to explore the present situation, the risk of fire occur and expand, and the fire damage. It also includes the limit fire protection and mitigation. In order to make a plan for fire protection and mitigation Khlong-Toei District was chosen as the case study, because it is one of the most fire occurred areas and the most of the fire damage to the public and the people around this area. Besides, this is the place where there are many factors for the fire to occar including ; 1) The factors that cause the fire to occur and expand. 2) The factors using the Geography Information System that prevent and mitigate the fire. The analysis found that most fire occurred from careless deeds. Most happened from low quality row-shelters. It also found that the population and the shelter density and the frequency of fore occur are the same. According to the study area, it is found that the areas of crowded population are around the port and oil tanks, which might effect from all the chemical matters and many danger matters from all the warehouse. The crowded area of populations and the rare of well-management and how they use all the area and land without good order that makes all the pollution such as old bad condition buildings, bad air ventilation, rare of space and narrow lanes. Most people are under educated, low income. When the fire occurred it usually brought great damage expand widely. The untidy and narrow road made it hard to reach the fire protection, this we call the bad obstruction for the fire-men and their fire-ambulance and equipment. From the study all the factors we can plan for the fire protection and mitigation for official and private organization that also set a standard and strict system to control dangerous and harmful chemical matter from their warehouse until they are loaded. Housing improvement is also a plan for the people to live a better life. Their home and belongings are also safe and much more protect and makes their lives better.